Antifungal Activity and Preliminary Phytochemical Analysis of Stem Bark Extracts of Juglans regia linn - UPADHYAY, VISHESH (International Journal of Pharmaceutical & Biological Archive, 2011)
Juglans regia, the royal species from Junglandaceae family, well-known for its valuable medicinal uses isgrown in the forests of Himalayas in India. It is a woody, deciduous and frost-tender tree. The root, stem bark, leaves, seeds, cotyledons and seed oil are useful to treat various health complaints including cancer in the folk medicines. The stem bark was collected from Upadhyay Orchards in Kullu (Himachal Pradesh) in May, 2010 and authenticated by Dr. K. MadhavaChetty, Asst. Prof., Dept. of Botany, Sri Venkateshwara University, Tirupathi (A.P). It was shade dried, powdered and extracted using different solvents viz., petroleum ether, benzene, chloroform, acetone, methanol, ethanol and distilled water in ascending order of polarity. Preliminary phyto-chemical screening of the crude extracts revealed the presence of carbohydrates, cardiac glycosides, flavanoids, steroids and tannins.Crude extract of the bark of Juglans regia Linn.were tested for antifungal activity by observing the zone of inhibition against four species of fungi. Antifungal activity was done by disc diffusion method at concentrations of 100, 200 and 300 ?é?Ág/ml/disc of the extracts, using ketoconazole(40?é?Ág/ml/disc) as the standard. The extracts showed selective fungistatic action against some species.All extractsshowed varying degrees of inhibitory activity against allfungal species. Methanolic extract showed significant activity against Aspergillus niger, Acetone extract significantly inhibited the growth of Alternalia alternata, Chloroform extract exhibited promising activity against Trichoderma virens and Fusariumsolani.